STAR FORMATION HISTORY IN THE GALACTIC THIN DISK - Marsakov, V. A.; Shapovalov, M. V.; Borkova, T. V. (Одеські астрономічні публікації, 2007)
We analyze the relations between the relative magnesium abundances in stars, [Mg/Fe], and their metallicities, Galactic orbital elements, and ages. The relative magnesium abundances in metal-poor thin-disk stars have been found to systematically decrease with increasing stellar orbital radii. This behavior suggests that, first, the star formation rate decreases with increasing Galactocentric distance and, second, there was no star formation for some time outside the solar circle while this process was continuous within the solar circle. The decrease in the star formation rate with increasing Galactocentric distance is responsible for the existence of a negative radial metallicity gradient (gradR[Fe/H]=(-0.05 ± 0.01) kpc -1) in the disk. At the same time the relative magnesium abundance exhibits no radial gradient. We discovered that in the thin disk there is not only the connection between age and metallicity, but between age and relative magnesium abundance also. It is in detail considered the influence of selective effects on the form of both age - metallicity and age - relative magnesium abundance diagrams. It is shown that the first several billion years of the formation of the thin disk interstellar medium in it was on the average sufficiently rich in heavy elements. At the same time the relative magnesium abundance exhibits no radial gradient. We discovered that in the thin disk there is not only the connection between age and metallicity, but between age and relative magnesium abundance also. It is in detail considered the influence of selective effects on the form of both age - metallicity and age - relative magnesium abundance diagrams. It is shown that the first several billion years of the formation of the thin disk interstellar medium in it was on average sufficiently rich in heavy elements ([Fe/H] ≈ -0.22), badly mixed (σ[Fe/H] ≈ 0.21), and the average relative magnesium abundance was comparatively high ([Mg/Fe] ≈ 0.10). Approximately 5 billion years ago average metallicity began to systematically increase, and its dispersion and the average relative magnesium abundance - to decrease. These properties may be explained by an increase in star formation rate with the simultaneous intensification of the processes of mixing the interstellar medium in the thin disk, provoke possible by interaction the Galaxy with the completely massive galaxy-satellite.